2019
DOI: 10.1186/s12896-019-0522-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of recombinant Mycobacterium tuberculosis antigens fused with cell wall-anchoring motif (LysM) from inclusion bodies using non-denaturing reagent (N-laurylsarcosine)

Abstract: Background The current limitations of conventional BCG vaccines highlights the importance in developing novel and effective vaccines against tuberculosis (TB). The utilization of probiotics such as Lactobacillus plantarum for the delivery of TB antigens through in-trans surface display provides an effective and safe vaccine approach against TB. Such non-recombinant probiotic surface display strategy involves the fusion of candidate proteins with cell wall binding domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Common prebiotics includes inulin, fructooligosaccharides (FOS), galactooligosaccharides (GOS), lactulose, and lafinose. Prebiotics from FOS are low-molecular-weight carbohydrates and only promote the growth of probiotics [ 24 ]. Prebiotics from GOS are short-chain oligosaccharides, resistant to the digestive process in the upper GI tract, with the following roles: i) support the selective development of beneficial cells in the intestinal microbiota; ii) maintain the structure and functions of the digestive system; iii) maintain immune balance by the development of lymphoid tissue associated with the intestine (GALT) that stores immune cells; iv) support the balance of the intestinal flora, which can be influenced by various factors (e.g., diet, lifestyle, stress) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common prebiotics includes inulin, fructooligosaccharides (FOS), galactooligosaccharides (GOS), lactulose, and lafinose. Prebiotics from FOS are low-molecular-weight carbohydrates and only promote the growth of probiotics [ 24 ]. Prebiotics from GOS are short-chain oligosaccharides, resistant to the digestive process in the upper GI tract, with the following roles: i) support the selective development of beneficial cells in the intestinal microbiota; ii) maintain the structure and functions of the digestive system; iii) maintain immune balance by the development of lymphoid tissue associated with the intestine (GALT) that stores immune cells; iv) support the balance of the intestinal flora, which can be influenced by various factors (e.g., diet, lifestyle, stress) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics from GOS are short-chain oligosaccharides, resistant to the digestive process in the upper GI tract, with the following roles: i) support the selective development of beneficial cells in the intestinal microbiota; ii) maintain the structure and functions of the digestive system; iii) maintain immune balance by the development of lymphoid tissue associated with the intestine (GALT) that stores immune cells; iv) support the balance of the intestinal flora, which can be influenced by various factors (e.g., diet, lifestyle, stress) [ 25 ]. The advantage of prebiotics is that they act synergistically with probiotics with symbiotic action and it is the most suitable option when an optimal repopulation of the flora is desired [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Reginald et al previously showed that Blo t 2 can be efficiently produced in a prokaryotic system, and a circular dichroism revealed that it had the appropriate secondary structure [ 6 ]. However, to increase protein yield, NLS, a mild detergent with few interferences on biological activity of recombinant proteins was used [ 34 , 35 ]. A more recent publication showed that this detergent may affect protein folding of insoluble proteins [ 36 ], then, the final impact on Blo t 2 is unknown.…”
Section: Discussionmentioning
confidence: 99%